Kernel estimation of entropy function under length-biased sampling. Issue 24 (17th December 2022) - Rajesh, G.; Sunoj, S. M.; Rajesh, Richu
Abstract: In this paper, we propose nonparametric kernel estimators for Shannon differential entropy function under length-biased sampling. Asymptotic properties of the estimators are established under suitable regularity conditions. A simulation study is accomplished to compare the performance of proposed estimators. The usefulness of the estimators are also examined using a real data.